Integrative taxonomic analysis reveals a new species of Leptobrachium (Anura: Megophryidae) from north-eastern Cambodia and central Vietnam. Issue 1 (17th January 2020) - Stuart, Bryan L.; Som, Hannah E.; Neang, Thy; Hoang, Huy Duc; Le, Duong Thi Thuy; Dau, Vinh Quang; Potter, Kathy; Rowley, Jodi J. L.
ABSTRACT: Species boundaries within the red-eyed Leptobrachium of southern Indochina have been uncertain. Leptobrachium pullum and L. mouhoti from upper and lower elevations, respectively, of the Langbian Plateau of southern Vietnam and eastern Cambodia differ in body size but have relatively low interspecific mitochondrial DNA divergence, leading to speculation that these might represent a single species with an elevational cline in body size. The recent discovery of an allopatric high-elevation population of red-eyed Leptobrachium on the Kon Tum Plateau (= Central Highlands) of north-eastern Cambodia and central Vietnam has been referred to both species, and to a putatively undescribed species. We examine variation in morphology of adults and tadpoles, mitochondrial DNA, 11 nuclear genes and advertisement calls, and show corroborating lines of evidence for the existence of three species of red-eyed Leptobrachium in southern Indochina. Although the three species are reciprocally monophyletic in mitochondrial DNA, their shallow mitochondrial DNA divergences are not mirrored by morphology, advertisement calls, or – in part – nuclear DNA, and probably reflect past mitochondrial introgression rather than recent speciation. The Central Highlands taxon is described herein as a new species. http://www.zoobank.org/urn:lsid:zoobank.org:pub:CE6650AF-D9FB-40F4-8A2E-9B4E23AAC205